(untitled) (Revista Española de Derecho Internacional, 2006)
The Rome Statute and the legal instruments which develop and implement it are showing the international community commitment to fulfil the gap existing in contemporary International Law as far as victims’ of serious crimes rights are concerned. Particularly, regarding victims’ right to reparation, compensation included. No matter how rewarding achievements may represent these and other international legal instruments, the result is clearly insufficient. In this study a research is developed to support the previous statement. Having analyzed the traditional position of victims of serious crimes against International Law and the latest development in establishing the first permanent International Penal Court in History, a bittersweet feeling remains in the reader: a lot achieved, much to reach for.